1982
DOI: 10.3109/01050398209076201
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Magnetic Fields: Source Location and ‘Tonotopical Organization’ in the Right Hemisphere of the Human Brain

Abstract: The late, acoustically evoked, averaged magnetic field from the right hemisphere of the human brain is composed of two signals. One is dominant, appears generated by an equivalent current dipole within or near the primary auditory cortex and shows a frequency dependent location and/or orientation (tonotopical organization). The other, denoted the 'residual' signal, resembles the electric T-complex and is possibly generated more diffusely in the auditory and adjacent cortical areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(43 citation statements)
references
References 13 publications
7
34
0
2
Order By: Relevance
“…This confirms previous results obtained by Elberling et al (1982), Romani et al (1982), Pantev et al (1988) and Yamamoto et al (1988), and it seems to be a reasonable value compared to the size of the area of the primary auditory cortex and integration region, which have a combined volume estimated to be approximately 2.5-3.5 cm 3 (Talairach and Tournoux 1988).…”
Section: Tonotopic Organization Of the Human Auditory Cortexsupporting
confidence: 77%
See 1 more Smart Citation
“…This confirms previous results obtained by Elberling et al (1982), Romani et al (1982), Pantev et al (1988) and Yamamoto et al (1988), and it seems to be a reasonable value compared to the size of the area of the primary auditory cortex and integration region, which have a combined volume estimated to be approximately 2.5-3.5 cm 3 (Talairach and Tournoux 1988).…”
Section: Tonotopic Organization Of the Human Auditory Cortexsupporting
confidence: 77%
“…That tonotopic organization is maintained throughout the central auditory pathway, including the primary auditory cortex, is known not only from animal studies (Merzenich and Brugge 1973;Merzenich et al 1975Merzenich et al , 1976Schreiner 1991) but also from human studies (Elberling et al 1982;Romani et al 1982;Lauter et al 1985;Pantev et al 1988Pantev et al , 1989Pantev et al , 1991aYamamoto et al 1988;Bertrand et al 1991). The depth of the source of the MlOO component of the slow AEF indicates the tonotopic organization of the auditory cortex: the higher the stimulus frequency, the deeper the equivalent source of the MlOO component.…”
Section: * Corresponding Authormentioning
confidence: 99%
“…Several studies have suggested that N1m originates from HeschlÕs Gyrus (Elberling et al, 1982;Reite et al, 1994); but the secondary auditory areas in the supratemporal plane are another possibility (Pantev et al, 1995;Lütkenhö ner and Steinsträter, 1998). It would be useful to compare the location of these activation sites with cyto-architectonic data in order to assess whether frequency-dependent activated areas are located in the same physiologically defined field, which would reflect tonotopy, or in separate fields, which would not point to any tonotopic organization (Schö nwiesner et al, 2002).…”
Section: Tonotopic Organization Of the Auditory Cortexmentioning
confidence: 99%
“…This procedure led to a model that was very similar to the initial one. Dipoles 1 and 2 are located in the superior temporal region, have a tangential orientation, and mainly reflect the activity of the primary auditory cortex (Elberling et al 1982;Hari et al 1980). Dipoles 3 and 4 are located in the lateral temporal lobe, have a radial orientation, and mainly reflect activity of the secondary auditory cortex (Arezzo et al 1975;Celesia 1976;Gallinat and Hegerl 1994;Scherg and von Cramon 1990).…”
Section: Dipole Source Analysismentioning
confidence: 99%